Higher education expansion & labour income inequality in high-income countries: A gender-specific perspective - Petra Sauer; Philippe Van Kerm; Daniele Checchi (Luxembourg Income Study (LIS), 2022)
The expansion of higher education since the second half of the 20th century was particularly pronounced among women. In most high-income countries to date more women complete a tertiary level than men. But research on the implications of higher education expansion for labour income inequality has largely treated expansion as gender neutral. With this paper we build on prior studies that have ignored potentially differential effects by factoring in what it means for earnings inequality to increase tertiary education among women as compared to men. To this end we draw on harmonised data from the Luxembourg Income Study (LIS) for 27 countries and two time points, 1995 and 2015, and use the method of Recentered Influence Function (RIF) regression. We obtain three main insights from our study. First, no average distributive effect of higher education expansion exists. Second, the distributive effect is gender-specific. The impact on the Gini coefficient of increasing tertiary attainment of men is positive and significant but the impact of increasing tertiary attainment of women is negative and significant. Third, the increasing share of tertiary educational attainment is the main factor explaining that distributive estimates shrink towards zero over time for both women and men. Only for men does larger inequality between and within educational groups significantly contribute to magnify the impact of educational expansion on earnings distributions across countries. Our analysis highlights that taking the gender dimension into account is crucial to obtain exhaustive understanding of the role of education for overall income inequality.
Keywords: 330; Education; Tertiary education; Inequality; Earnings; Gender